Cooperation beyond consanguinity: post-marital residence, delineations of kin and social support among South Indian Tamils. (2nd September 2019) - Power, Eleanor A.; Ready, Elspeth
Abstract : Evolutionary ecologists have shown that relatives are important providers of support across many species. Among humans, cultural reckonings of kinship are more than just relatedness, as they interact with systems of descent, inheritance, marriage and residence. These cultural aspects of kinship may be particularly important when a person is determining which kin, if any, to call upon for help. Here, we explore the relationship between kinship and cooperation by drawing upon social support network data from two villages in South India. While these Tamil villages have a nominally male-biased kinship system (being patrilocal and patrilineal), matrilateral kin play essential social roles and many women reside in their natal villages, letting us tease apart the relative importance of genetic relatedness, kinship and residence in accessing social support. We find that people often name both their consanguineal and affinal kin as providing them with support, and we see some weakening of support with lesser relatedness. Matrilateral and patrilateral relatives are roughly equally likely to be named, and the greatest distinction instead is in their availability, which is highly contingent on post-marital residence patterns. People residing in their natal village have many more consanguineal relatives present than those who have relocated. Still, relocation has only a small effect on an individual's network size, as non-natal residents are more reliant on the few kin that they have present, most of whom are affines. In sum, marriage patterns have an important impact on kin availability, but the flexibility offered by the broadening of the concept of kin helps people develop the cooperative relationships that they rely upon, even in the absence of genetic relatives. This article is part of the theme issue 'The evolution of female-biased kinship in humans and other mammals'.